A Bibliometric Analysis of Global Scientific Research on Scrub Typhus. (17th October 2020) - Musa, Taha Hussein; Ahmad, Tauseef; Li, Wei; Kawuki, Joseph; Wana, Mohammed Nasiru; Musa, Hassan Hussein; Wei, Pingmin
Abstract : Objective . The rise of zoonotic diseases has become a global health issue around the world. The present study is aimed at assessing the global status and the trends in scrub typhus (ST) research. Methods . Publications related to ST studies from 1945 to 21 st July 2020 were retrieved from the Scopus database. The search for the ST literature was conducted using the entry terms of the MeSH (Medical Subject Headings) database. Full research articles and reviews were included in the analysis, and no limitation to the language was specified. Key bibliometric indicator analysis was performed using Microsoft Excel, Bibliometrix (an R package), GraphPad Prism 5, and VOSviewer (version 1.6.6). Results . A total of 1567 publications were retrieved. The results revealed a significant increase in the number of ST publications over time. The documents received an average of 11.22 citations per document. Mahidol University in Thailand (258, 16.46%) was the most productive institution, while the American Journal of Tropical Medicine and Hygiene published the most ST articles (88, 5.62%). Korea (195, 12.44%) was the most productive country, followed by India (178, 11.36%) and China (106, 6.76%). Richards AL was the most productive author with 36 articles. Conclusions . The study findings provide useful insights into the global efforts and works related to the progress of ST research, which can be used to identify future research areas, such as vaccine development.